2019
DOI: 10.4103/jrpp.jrpp_18_32
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of medication package inserts in Iran

Abstract: Objective: Package inserts (PIs) provide information for the safe and effective use of medication. There is no study on the evaluation of PIs in Iran. The purpose of this study was to evaluate the completeness of PIs supplied with the 100 top-selling medications in Iran. Methods: This cross-sectional observational study was conducted during 3 weeks in January 2017. One hundred medications were chosen from a list supplied by the Iran Food and Drug Administration (IFDA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The limited availability of PIs in Iran was confirmed in another study of 100 commonly used medicines, 63% of which had a PI [ 126 ] and none of which met all local regulatory requirements, with the authors suggesting superior WMI accompanied imported products. Additional studies found missing information in 104 PIs for psychiatric drugs [ 125 ], that 92 PIs for neurological drugs failed to fully meet Iran’s local requirements [ 127 ] and that the readability of 71% of 33 PIs was graded as difficult [ 124 ].…”
Section: Resultsmentioning
confidence: 96%
“…The limited availability of PIs in Iran was confirmed in another study of 100 commonly used medicines, 63% of which had a PI [ 126 ] and none of which met all local regulatory requirements, with the authors suggesting superior WMI accompanied imported products. Additional studies found missing information in 104 PIs for psychiatric drugs [ 125 ], that 92 PIs for neurological drugs failed to fully meet Iran’s local requirements [ 127 ] and that the readability of 71% of 33 PIs was graded as difficult [ 124 ].…”
Section: Resultsmentioning
confidence: 96%
“…Examining the quality of the information provided in the DL is substantial, as the presence of obvious details in the leaflet will help the patient use the medication correctly (Gillies et al, 2014). Evaluation of the information content of the DLs was carried out in many previous studies (Al-Aqeel, 2012;Arandy et al, 2019;Chhaya, 2017;Eshtayeh et al, 2019;Khamas et al, 2019;Qatmosh et al, 2017;Rahim & Rafiq, 2013;Shivkar, 2009). Some of these depended on the presence of particular topics in the PIs (Al-Aqeel, 2012;Chhaya, 2017;Khamas et al, 2019;Rahim & Rafiq, 2013;Shivkar, 2009), while other studies built their assessment on both the presence of certain headings and the amount of information provided in the PIs (Arandy et al, 2019;Eshtayeh et al, 2019;Qatmosh et al, 2017;.…”
Section: Introductionmentioning
confidence: 99%
“…Examining the quality of the information provided in the DL is substantial, as the presence of obvious details in the leaflet will help the patient use the medication correctly (Gillies et al, 2014). Evaluation of the information content of the DLs was carried out in many previous studies (Al-Aqeel, 2012; Arandy et al, 2019; Chhaya, 2017; Eshtayeh et al, 2019; Khamas et al, 2019; Qatmosh et al, 2017; Rahim & Rafiq, 2013; A. Sawalha et al, 2008; Shivkar, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations